1994
DOI: 10.1084/jem.180.6.2239
|View full text |Cite
|
Sign up to set email alerts
|

T cells reactive to an inducible heat shock protein induce disease in toxin-induced interstitial nephritis.

Abstract: SummaryT cells reactive against immunodominant regions of inducible heat shock proteins (HSPs) have been identified in the chronic inflammatory lesions of several experimental autoimmune diseases. Since HSPs are known to be induced by a number of renal tubular epithelial cell toxins associated with chronic interstitial nephritis, we investigated the relevance of HSP expression and T cell reactivity to HSP70 in a model of progressive inflammatory interstitial nephritis. Chronic administration of cadmium chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 51 publications
1
18
1
Order By: Relevance
“…Furthermore, Hsp60, unlike Hsp70 and gp96, does not seem to introduce chaperoned peptides into the cross-presentation pathway, which could recruit CD8 T cells as effectors. T cell responses against Hsp70 have been shown to be important in CdCl 2 -induced interstitial nephritis (37), and T cells specific for Hsp60 have been shown to contribute to colitis in immunocompromised mice (38). However, if this played a role in the present study, then it would be difficult to explain why pathology was confined to the kidney and why systemic administration of Hsp60 alone did not cause any pathology.…”
Section: Discussioncontrasting
confidence: 49%
“…Furthermore, Hsp60, unlike Hsp70 and gp96, does not seem to introduce chaperoned peptides into the cross-presentation pathway, which could recruit CD8 T cells as effectors. T cell responses against Hsp70 have been shown to be important in CdCl 2 -induced interstitial nephritis (37), and T cells specific for Hsp60 have been shown to contribute to colitis in immunocompromised mice (38). However, if this played a role in the present study, then it would be difficult to explain why pathology was confined to the kidney and why systemic administration of Hsp60 alone did not cause any pathology.…”
Section: Discussioncontrasting
confidence: 49%
“…HSPs themselves can be the cause of autoimmune disease. For example, Weiss et al (149) showed that T cells reactive against HSPs can induce interstitial nephritis. In addition, HSPs are known to bind peptides in damaged tissue to form HSP-peptide complexes with strong immunogenicity (27,142).…”
Section: Does T Cell Infiltration In the Renal Interstitium Reflect Amentioning
confidence: 98%
“…The most compelling evidence comes from observing the sequence of events that follow cadmium-induced renal injury in mice. The tubules that have been damaged by cadmium express heat shock protein 70 de novo, which in turn activates T cells and results in interstitial nephritis [29]. Passive transfer of these sensitized T cells to normal mice induces interstitial nephritis.…”
Section: Cellular Activation and Injury Phasementioning
confidence: 99%